2010
DOI: 10.4103/0973-1296.66939
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical investigation and antimicrobial activity of Psidium guajava L. leaves

Abstract: Psidium guajava L. leaves were subjected to extraction, fractionation and isolation of the flavonoidal compounds. Five flavonoidal compounds were isolated which are quercetin, quercetin-3-O-α-L-arabinofuranoside, quercetin-3-O-β-D-arabinopyranoside, quercetin-3-O-β-D-glucoside and quercetin-3-O-β-D-galactoside. Quercetin-3-O-β-D-arabinopyranoside was isolated for the first time from the leaves. Fractions together with the isolates were tested for their antimicrobial activity. The antimicrobial studies showed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 11 publications
8
57
0
2
Order By: Relevance
“…In previous studies methanolic extracts suppressed the growth of S. aureus and E. coli (Doughari and Manzara, 2008). Ethanol extracts isolated flavonoid compounds that were effective against S. aureus and E. coli (Metwally, 2010). Contrary results on the activity of methanolic leaf extracts was reported by (Gaidem et al, 2010) where by the extracts had no effect on the growth E. coli, S. aureus and S. fecalis .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies methanolic extracts suppressed the growth of S. aureus and E. coli (Doughari and Manzara, 2008). Ethanol extracts isolated flavonoid compounds that were effective against S. aureus and E. coli (Metwally, 2010). Contrary results on the activity of methanolic leaf extracts was reported by (Gaidem et al, 2010) where by the extracts had no effect on the growth E. coli, S. aureus and S. fecalis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this could help determine whether the previously reported low IVOMD (Adrian et al 2012) has an impact on mineral absorption. The lack of nutrient availability and compromise of animal health could increase due to the presence of antimicrobial factors (Metwally et al 2010), resulting in limited digestibility of pasture grasses (Adrian et al 2012). Researchers in India looked at twenty-four crossbred (Large White Yorkshire × Desi) male pigs and found that adding sun-dried guava pomace (up to 30 percent) to their diets did not significantly affect growth and carcass characteristics (Madhava et al 2004).…”
Section: Correlations Of Macrominerals Between Guava and Soilmentioning
confidence: 98%
“…Muller Hinton agar (MHA) plates were prepared by pouring 15 ml of molten media into sterile petriplates [20][21][22]. The fresh grown bacteria were suspended in sterile saline to achieve concentration of 10 7 CFU/ml.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%